Potensi implementasi skema payment for environmental services Ruang Terbuka Hijau Taman Lembah Mawar - Tasya Nabila Siregar; Asti Istiqomah (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2022)
Land conversion reduce the Green Open Space (RTH) and provoke environmental problems. In Law No.26/2007 every city must have RTH at least 30% of the total area. RTH Depok City currently only reaches 16.33%. The objectives of this study are (1) identify the public perception of the existence of RTH Taman Lembah Mawar, (2) estimate the Willingness to Pay (WTP), (3) identify the potential implementation of the Payment For Environmental Services (PES). The method used is a Likert scale, DC-CVM, and descriptive analysis. The results show that the public's perception of the existence of Lembah Mawar Park is very good. WTP is IDR 13,147/household/year. Factors that have a significant effect are bid, education level, income level, and distance. PES scheme can be carried out using a voluntary or mandatory scheme with a participation fee collection mechanism through an institution formed by the community and supervised by the City Government.